INTRODUCING INTERNET OF THINGS (IOT) FOR A COMMUNITY VILLAGE BASED ON INDUSTRIAL REVOLUTION 4.0 - Sulistiyanti, Sri Ratna; Setyawan, F.X. Arinto; Komarudin, M.; Warsono, Warsono (Journal of Community Research and Service, 2018)
AbstractA house is a gathering place for a family, where each family member has a different passion and busyness. If at any time a family member is traveling and wants to monitor and control conditions from a distance, an electronic device is used. One solution to determine the condition of home security at all times, an internet connection is needed by using the concept of the Internet of Things (IoT). IoT is a concept of using an internet network to transfer data or share information with certain applications. The IoT concept is one of the IR 4.0 based systems. In Indonesia, the system has not been widely implemented, especially for village areas. The purpose of this activity is to introduce the concept of IoT in a region as a system of monitoring and controlling homes. The method used is socialization and training of IoT-based smart home models. The system that is introduced is setting lights, monitoring gas (kitchen security), and monitoring using a camera. The results obtained were an increase in knowledge from 45.4% to 79%, and increased skills from 33% to 63%.Keywords: IoT, Village, Industrial Revolution 4.0.